Analisis Perkembangan E-Business Dalam Pemanfaatan Media Sosial Tiktok Shop - Ira Yanti; Nurhapirah Tasnim; Riska Febrianti Aulia; Nurbaiti (Jurnal Ekonomi dan Bisnis Digital, 2022)
At this time, technological developments are very fast, especially those related to social media networks, at this time it is impossible not to meet people who do not use technology in their daily lives, from children to adults. TikTok is people's choice to market their business. Social media certainly plays an important role today. Social media can be used to market the business we have. Tiktokshop is a marketing medium that can increase sales turnover. Tiktokshop is not only an entertainment medium, but also a sales platform. In the Tiktokshop application, traders make selling videos as best they can. The aim of this research is to find out how much benefit TikTok has for business development. The research method used in this research is a qualitative method and uses a library approach by relying on available articles and journals and how business people respond to those who use the TikTok Shop application.